2022
DOI: 10.1186/s12889-022-13788-4
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic analysis of short-term trends of COVID-19: modeling and data analytics

Abstract: Background COVID-19 caused a worldwide outbreak leading the majority of human activities to a rough breakdown. Many stakeholders proposed multiple interventions to slow down the disease and number of papers were devoted to the understanding the pandemic, but to a less extend some were oriented socio-economic analysis. In this paper, a socio-economic analysis is proposed to investigate the early-age effect of socio-economic factors on COVID-19 spread. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Taken together, all these negative manifestations lead to a decline in performance, by undermining medical productivity, especially in less developed countries. Financial expenses in the public sector call for a detailed oversight to properly balance inputs and outputs [ 29 , 43 ]. Moreover, in times of crisis, adequate management is required, which does not allow for even greater deviations in terms of wasting resources.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, all these negative manifestations lead to a decline in performance, by undermining medical productivity, especially in less developed countries. Financial expenses in the public sector call for a detailed oversight to properly balance inputs and outputs [ 29 , 43 ]. Moreover, in times of crisis, adequate management is required, which does not allow for even greater deviations in terms of wasting resources.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given that the right to life is universal, an approach by which states in difficulty in procuring vaccines be supported should be found. By reporting to the level of development of a country, some studies have shown that gross domestic product (GDP) per capita influences the COVID-19 spread and vaccination of the population [ 24 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the estimation of the optimal number of clusters k * can be carried out by means of a change-point algorithm. In this paper, a Point-Wise-Procedure (PWP) algorithm was adopted to catch the optimal number of clusters, PWP algorithm was developed by [31] in order to select change-points by means of the inferential analysis procedure of the fitting error of a given set of point. Other reliable change-point procedures can be exploited for this purpose apart the PWP heuristic.…”
Section: Inference Statistics Of 𝝉 * and Main Workflow Of The Gic Heu...mentioning
confidence: 99%
“…The classical pandemic models, first of all SIR, SEIR and SIRD, have been extensively used in the modeling of the COVID-19 pandemic in order to understand and predict the transmission dynamics of the disease (see, e.g., [16][17][18][19][20][21]). In particular, these models and their variants can be used to estimate key epidemiological parameters of COVID-19, such as the basic reproduction number R 0 (see, e.g., [18,22,23]).…”
Section: Introductionmentioning
confidence: 99%